Gray platelet syndrome. Dissociation between abnormal sorting in megakaryocyte alpha-granules and normal sorting in Weibel-Palade bodies of endothelial cells. - Gebrane-Younès, J (1993)
The gray platelet syndrome (GPS) is a rare congenital bleeding disorder in which megakaryocytes and platelets are deficient in alpha-granule secretory proteins. Since the Weibel-Palade bodies (WPB) of endothelial cells as well as the alpha-granules contain the von Willebrand Factor (vWF) and P-selectin, we examined by transmission electron microscopy the dermis capillary network of two patients with GPS. Endothelial cells showed the presence of normal WPB with typical internal tubules. Using single and double immunogold labeling for vWF and P-selectin, we detected vWF within WPB, where it was codistributed with the tubules, whereas P-selectin delineated the outline of WPB. Therefore, the fundamental targeting defect in GPS is specific to the megakaryocytic cell line.